e^{-qx}/(1-ae^{-px})[0,∞]などの定積分

\begin{alignat}{2}
&(1) \displaystyle\int_0^{\infty} \frac{e^{-qx}}{1-ae^{-px}}dx=\displaystyle\sum_{n=0}^{\infty} \frac{a^n}{pn+q}  (0 \lt a \lt 1, p,q \gt 0)\\
&(2) \displaystyle\int_0^{\infty} \frac{e^{-x}-e^{(p-1)x}}{1-e^{-x}}dx=ψ(1-p)+γ  (0 \lt p \lt 1)\\
&(3) \displaystyle\int_0^{\infty} \frac{e^{-x}-e^{-px}}{1-e^{-x}}dx=ψ(p)+γ  (p \gt 0)\\
&(4) \displaystyle\int_0^{\infty} \frac{e^{-px}-e^{-qx}}{1-e^{-x}}dx=ψ(q)-ψ(p)  (p,q \gt 0)\\
\end{alignat}









<証明>

\begin{alignat}{2}
&(1) \displaystyle\int_0^{\infty} \frac{e^{-qx}}{1-ae^{-px}}dx=\displaystyle\int_0^{\infty}\left\{\displaystyle\sum_{n=0}^{\infty} (ae^{-px})^n\right\}dx=\displaystyle\sum_{n=0}^{\infty} a^n\displaystyle\int_0^{\infty} e^{-(np+q)x}dx\\
&                   =\displaystyle\sum_{n=0}^{\infty} a^n \left[-\frac{e^{-(np+q)x}}{np+q}\right]_0^{\infty}=\displaystyle\sum_{n=0}^{\infty} \frac{a^n}{pn+q}
\end{alignat}以上より$$\displaystyle\int_0^{\infty} \frac{e^{-qx}}{1-ae^{-px}}dx=\displaystyle\sum_{n=0}^{\infty} \frac{a^n}{pn+q}$$







\((2)(3)(4)\) は全て \(e^{-x}=t\) と置きます。\(\displaystyle \left( -x=\log t, dx=-\frac{1}{t}dt\right)\)

\begin{alignat}{2}
&(2) \displaystyle\int_0^{\infty} \frac{e^{-x}-e^{(p-1)x}}{1-e^{-x}}dx=\displaystyle\int_1^0 \frac{t-t^{1-p}}{1-t}\left(-\frac{1}{t}\right)dt=\displaystyle\int_0^1 \frac{1-t^{-p}}{1-t}dt\\
&\\
&                     =ψ(1-p)-ψ(1)=ψ(1-p)+γ\\
&\\
&\\
&(3) \displaystyle\int_0^{\infty} \frac{e^{-x}-e^{-px}}{1-e^{-x}}dx=\displaystyle\int_1^0 \frac{t-t^p}{1-t}\left(-\frac{1}{t}\right)dt=\displaystyle\int_0^1 \frac{1-t^{p-1}}{1-t}dt\\
&\\
&                   =ψ(p)-ψ(1)=ψ(p)+γ\\
&\\
&\\
&(4) \displaystyle\int_0^{\infty} \frac{e^{-px}-e^{-qx}}{1-e^{-x}}dx=\displaystyle\int_1^0 \frac{t^p-t^q}{1-t}\left(-\frac{1}{t}\right)dt=\displaystyle\int_0^1 \frac{t^{p-1}-t^{q-1}}{1-t}dt=ψ(q)-ψ(p)\\
\end{alignat}

コメントを残す

メールアドレスが公開されることはありません。 * が付いている欄は必須項目です